Assessing the Unterberger test: introduction of a novel smartphone application. Issue 11 (November 2014) - Whittaker, M; Mathew, A; Kanani, R; Kanegaonkar, R G
Abstract Background: Peripheral vestibular function is commonly assessed using the Unterberger test. Patients are asked to march on the spot and their extent of rotation is recorded. The sensitivity of this test depends on an assessor accurately estimating the degree of rotation. This study therefore aimed to compare observer estimates with a smartphone application (DplusR Balance) that accurately records rotation. Method: Twenty-five participants were asked to estimate the degree of rotation in 10 successive Unterberger tests performed by a volunteer. Results: The average difference between estimated and application recorded extent of rotation was 30°. Conclusion: Assessors poorly estimate the degree of rotation in this clinical test, to an extent sufficient to affect clinical interpretation and diagnosis. We recommend the use of this application or alternative methods to record the degree of rotation in patients.